The emergence of fur money in medieval Russia - Huletski, Dzmitry (KOINON: The International Journal of Classical Numismatic Studies, 2020)
Written sources of Ancient Rus’ record the developed monetary system of Pre-Mongol Rus’, consisting of a clearly defined circle of ‘denominations’. At first, it’s grivna (гривна), nogata (ногата), kuna (куна), and veksha (векша). In documents of northern origin, rezana is also present. In the 12th century, when, according to the scholars, the development of commodity-money relations in Kievan Rus’ reached its highest peak, various types of grivnas — ‘of silver’, ‘of kunas’, ‘of sables’, and even ‘of dranitsy’ (драницы) (torn and worn skins) appeared.